KEUNGGULAN KOMPARATIF USAHATANI PADI PADA BERBAGAI POLA AGROEKOSISTEM DI KABUPATEN MEMPAWAH - Irham, Adi Suyatno, Masyhuri, Jangkung Handoyo Mulyo, (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2014)
This research was conducted in the District of Mempawah, which is in the region of West Kalimantan and borders with neighboring countries (Malaysia), which of course has special characteristics, especially from the aspect of international trade, so that the comparative advantage of paddy associated with aspects of international trade, need to be examined. This study used a survey method, with 183 sample, where the number of samples of each pattern of agro-ecosystem isirrigation pattern has 55 samples, tidal patterns has 42 samples, rainfedpatterns has46samples and dry land patterns has 40 samples. The method of analysis in this study used the concept of DRC (Domestic Resource Cost). The results showed comparative advantage as indicated by the average value of the DRC is Rp 2,429, - This value indicates that the cost of domestic resources for the value to produce rice, can save foreign exchange worth US 1. DRCR average of 0, 24 which means rice farming has a comparative advantage (<1). Irrigation schemes have the highest levels of comparative advantage and the dry land pattern has the lowest level of comparative advantage. DRCR shows that rice is still cheaper economically to be produced in the country compared with imports from other countries. The implications of this conclusion is that the spur policy (increase) in rice production in the District of Mempawah still favorable compared to the expense of foreign exchange to import the commodity from other countries. Keywords: comparative advantage, Pattern Agroecosystems, Domestic Resource Cost